Social Practices Of Personal Naming Among Parents In Rural And Urban Societies In Irbid, Jordan: A Socioonomastics And Morphological Study - Mohammad Ali Tahat, Abdel Razzaq (2022)
Taking into account the scarcity of research on the practices of personal naming in Jordan, this study examined personal names in rural and urban regions in Irbid, Jordan, in terms of social practices, factors affecting the social practices, and morphological patterns. The research approach of this study is mixed-methods in which the design is explanatory sequential design with two phases: quantitative and qualitative. The sample of this study is 384 parents who were randomly selected from urban and rural regions in Irbid. In the quantitative phase, data were collected using an adapted questionnaire which consists of three parts: Part A (demographic variables with 5 items), Part B (the social practices of personal naming with 16 items), and Part C (factors affecting the social practices of personal naming). In the qualitative phase, qualitative data were collected through semi-structured interviews which were constructed and designed based on the results of the questionnaire to provide elaboration and explanation for the results obtained from the quantitative phase.